2021
DOI: 10.9734/jpri/2021/v33i42a32386
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge, Attitude, and Perception towards COVID-19 Vaccine among the General Population in the Hail Province, KSA

Abstract: Aim: Coronavirus infection has caused disease at the pandemic level with several deaths worldwide and affected all aspects of human life. One way to minimize virus transmission and its effects is to perform mass vaccination within the general population so that herd immunity is developed against the SARS-CoV-2 virus. However, low health literacy and vaccine hesitancy are potential threats in achieving this. The present study is designed to measure the Knowledge, Attitude, and Perception levels towards COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…Generally, the participants had low knowledge of the COVID 19 virus and vaccine. A similar finding was reported by Mohamed et al, in Malaysia and Enitan et al, in six geopolitical zones in Nigeria, where they reported poor knowledge about the COVID-19 vaccine (Mohamed et al, 2021;Enitan et al, 2020) However, this finding is at variance with the reports of Khaja et al, in Saudi Arabia, and Huynh et al, in Vietnam, where they reported adequate knowledge of COVID-19 Virus and vaccine among their participants (Khaja et al, 2021;Huynh et al, 2021) This difference in finding may be as a result of disparity in study location and population, also the effort of government and non-governmental agencies in the countries to ensure that the populace is well informed about COVID-19 virus.…”
Section: Discussionsupporting
confidence: 78%
“…Generally, the participants had low knowledge of the COVID 19 virus and vaccine. A similar finding was reported by Mohamed et al, in Malaysia and Enitan et al, in six geopolitical zones in Nigeria, where they reported poor knowledge about the COVID-19 vaccine (Mohamed et al, 2021;Enitan et al, 2020) However, this finding is at variance with the reports of Khaja et al, in Saudi Arabia, and Huynh et al, in Vietnam, where they reported adequate knowledge of COVID-19 Virus and vaccine among their participants (Khaja et al, 2021;Huynh et al, 2021) This difference in finding may be as a result of disparity in study location and population, also the effort of government and non-governmental agencies in the countries to ensure that the populace is well informed about COVID-19 virus.…”
Section: Discussionsupporting
confidence: 78%